The Relationship between Exclusive Breastfeeding and Clean Water with Stunting in Toddlers - Lanita, Usi; Cardea Al Nabila, Pamella; Hidayati, Fajrina; Astuti Siregar, Sri; Kasyani, Kasyani (Rifa'Institute, 2023)
Introduction: Stunting is an acute nutritional problem where a child's height does not match their age. Stunting is caused by a variety of factors. The incidence of stunting in Jambi Province is still quite high, especially in East Tanjung Jabung Regency, namely at the Simpang Pandan Community Health Center, with a prevalence of 24.58%. Objective: This research aims to determine the relationship between exclusive breastfeeding and clean water and the incidence of stunting. Method: This study aims to determine the relationship between exclusive breastfeeding and clean water and the incidence of stunting. Results and Discussion: The results of the research show that there is no relationship between exclusive breastfeeding and the incidence of stunting in toddlers, and there is a relationship between access to clean water and the incidence of stunting in toddlers in the working area of the Simpang Pandan Jambi Community Health Center. Conclusions: There is a relationship between access to clean water and the incidence of stunting in toddlers